2020
DOI: 10.1186/s12985-020-1288-4
|View full text |Cite
|
Sign up to set email alerts
|

Porcine β-defensin 2 inhibits proliferation of pseudorabies virus in vitro and in transgenic mice

Abstract: Background: Porcine β-defensin 2 (PBD-2), produced by host cells, is an antimicrobial cysteine-rich cationic peptide with multi-functions. Previous studies have demonstrated that PBD-2 can kill various bacteria, regulate host immune responses and promote growth of piglets. However, the antiviral role of PBD-2 is rarely investigated. This study aimed to reveal the antiviral ability of PBD-2 against pseudorabies virus (PRV), the causative pathogen of Aujeszky's disease, in PK-15 cells and in a PBD-2 expressing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
2
12
0
1
Order By: Relevance
“…As a major group of cationic peptides widely existing in animals, defensins have been proven to possess broad antimicrobial activities against different pathogens including bacteria, fungi and viruses. Our previous in vivo studies showed that pigs overexpressing PBD-2 displayed increased resistance to A. pleuoropneumoniae infection [ 16 ], while mice expressing PBD-2 became more resistant to pseudorabies virus and Salmonella Typhimurium infections [ 27 , 28 ]. Given that the previous pbd-2 TG pigs were produced using random gene insertion, which also introduced a SMG, these would raise public concern on the biosafety of TG animals and hamper the commercialization of TG animals derived products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a major group of cationic peptides widely existing in animals, defensins have been proven to possess broad antimicrobial activities against different pathogens including bacteria, fungi and viruses. Our previous in vivo studies showed that pigs overexpressing PBD-2 displayed increased resistance to A. pleuoropneumoniae infection [ 16 ], while mice expressing PBD-2 became more resistant to pseudorabies virus and Salmonella Typhimurium infections [ 27 , 28 ]. Given that the previous pbd-2 TG pigs were produced using random gene insertion, which also introduced a SMG, these would raise public concern on the biosafety of TG animals and hamper the commercialization of TG animals derived products.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial mechanism of PBD-2 was elucidated in Escherichia coli , being disruption of the membrane integrity and affecting the DNA transcription and translation when PBD-2 entered into the cytoplasm [ 25 ]. Previous studies described that PBD-2 could hamper PRRSV replication in vitro [ 26 ] and suppress proliferation of pseudorabies virus both in vitro and in TG mice [ 27 ]. Besides, PBD-2 has been identified to alleviated inflammation by binding toll-like receptor 4 and inhibiting the subsequent NF-κB activation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examples also include the insertion of an extra copy of the porcine CD28 gene into the genome, which improved the protective immune responses to PRRSV infection in pigs [ 62 ]. In addition to the described antibacterial activities of PBD-2, previous studies have demonstrated that PBD-2 could inhibit the proliferation of two major swine viruses, PRRSV and PRV, in different cell models [ 6 , 17 ]. These prompt us to investigate whether PBD-2 TG pigs can resist swine viral pathogen infections in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that PBD-2 could provide protection against S. Typhimurium infection in TG mice through direct bactericidal ability and the inactivation of the TLR4/NF-κB pathway [ 16 ]. In addition, mice expressing PBD-2 became more resistant to pseudorabies virus (PRV) infection [ 17 ], while pigs overexpressing PBD-2 obtained improved resilience to Actinobacillus pleuropneumoniae infection [ 18 ]. Additionally, fibroblasts from our recently produced PBD-2 TG pigs displayed enhanced resistance to both Streptococcus suis and A. pleuropneumoniae infections [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…After mice were infected with PRV, histopathological analysis found that the brain, spleen, and liver tissues had different degrees of lesions [45]. Studies have shown that PRV could cause lethal respiratory disease in an animal model of PRV-infected BALB/c mice [46].…”
Section: Discussionmentioning
confidence: 99%